POETIC COMBINATIONS OF TRINITY AND FIVE SYMBOLS IN EXAMPLES OF UZBEK AND WORLD FOLKLORE (Scientific journal of the Fergana State University, 2024)
It is known that the world we live in is made up of a chain of numbers, and we cannot imagine this world without numbers. In this small study, special attention is paid to revealing the subtle aspects of the meaning of the numbers three and five, which are not known to science. In the article, various combinations of symbols of threes and fives reflect the life and characteristics of a certain nation, the scientific term, significant features, artistic aspects, history of origin, evolution, and functional aspects of the number are defined. The analysis of the triple and pentad images found in the examples of Uzbek and world folklore is also expressed.